TOXICITY PROFILE OF CELASTRUS PANICULATUS SEEDS: A PRECLINICAL STUDY - MISHRA, BHARAT; JOHN, ELEZABETH; JOY, KRUPAMOL; R, BADMANABAN; R, ALEESHA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to evaluate the toxicity profile of Celastrus paniculatus (CP) by performing a preclinical study on Swiss albino mice and demonstrate a safety description through monitoring their autonomic, neurological, behavioral, physical, and biochemistry profiles. Methods: The toxicity profiles (acute and subacute) of CP were evaluated using Swiss albino mice in which they were divided into four groups: Group I received 1% Tween 20 and dimethyl sulfoxide. Group II, III, and IV received CP seed oil orally, at doses of 300, 2000, and 5000 mg/kg body weight for both acute and subacute toxicity studies in accordance with Organization for Economic Cooperation and Development guidelines No. 423. Special attention was given during the first 4 h and daily thereafter for a total of 14 days. Behavioral profile, physical state changes, and other parameters such as tremors, convulsion, lethargy were noted. Clinical signs were observed daily during the 28 days of the treatment period. Body weights were measured once a week. On the 29th day, the animals were kept to overnight and blood samples were collected through retro-orbital puncture for biochemical analysis. Results: In both acute and subacute toxicity studies, the treatment with CP did not affect the normal health status of animals. It is suggestive that CP is considered practically non-toxic. Conclusion: The toxicity profile of CP seed oil was evaluated and found to be safe until 2000 mg/kg dose.